The orogenic wedge in the central Scandinavian Caledonides: scandian structural evolution and possible influence on the foreland basin - Greiling, Reinhard O.; Garfunkel, Zvi; Zachrisson, Ebbe (GFF online, 1998)
The orogenic wedge of the central Scandinavian Caledonides - overlying the Baltic Shield without a substantial foreland basin - is built up of a stack of nappes, which are divided here into three mechanically distinct tiers: A: Lower Allochthon with exclusively Scandian (Middle to Late Silurian) structures and metamorphism, B: Middle Allochthon and Seve units of Upper Allochthon with traces of Finnmarkian (Early Ordovician) events, and C: overlying exotic terranes (Köli units of Upper Allochthon, Uppermost Allochthon). Detailed structural work documented shear criteria at the tier B-C (Seve-Köli) boundary, which consistently indicate a down-dip, top-to-the-west movement at a regional scale and immediately after peak PT conditions (c. Late Wenlockian). Subsequently, the Seve-Köli boundary was deformed by regional folds, caused by the stacking of thrust systems in the underlying Lower Allochthon. Due to lithology and early cooling, the tier B of the Caledonian orogenic wedge is dominated by strong rocks, whereas the lower tier (A), containing a number of horizons with low friction, is of relatively weaker strength. For the orogenic wedge as a whole, the contrast in strength between tiers A and B gave rise to a relatively flat toe of the wedge and a small frontal load. The model of a tiered wedge with a toe is proposed here as an explanation for the small frontal depression and foreland basin along the eastern margin of the north-central Scandinavian Caledonides.
Elektronische Reproduktion der Druck-Ausgabe vom 6. August 2009
Gesehen am 03.11.2022